Hierarchically porous, and Cu- and Zn-containing γ-AlOOH mesostrands as adjuvants for cancer immunotherapy. Issue 1 (December 2017) - Li, Xia; Shenashen, Mohamed; Wang, Xiupeng; Ito, Atsuo; Taniguchi, Akiyoshi; EI-Safty, Sherif
Abstract Alum is the only licensed adjuvant by Food and Drug Administration of USA used in many human vaccines and has excellent safety record in clinical applications. However, alum hardly induces T helper 1 (Th1) immune responses that are required for anti-tumor immunity. In the present study, we fabricated hierarchical copper- and zinc- buds dressing γ-AlOOH mesostrands (Cu- and Zn-AMSs) with randomly wrinkled morphology, mesoscale void- or cave-like pockets, high-exposed surface coverage sites, and positive charge streams in saline. We confirmed that Cu- and Zn-AMSs promoted intracellular uptake of model cancer antigen (ovalbumin, OVA) by THP-1-differentiated macrophage-like cellsin vitro . Moreover, Cu- and Zn-AMSs enhanced maturation and cytokine release of bone marrow dendritic cellsin vitro .In vivo study demonstrated that Cu- and Zn-AMSs markedly induced anti-tumor-immunity and enhanced CD4 + and CD8 + T cell populations in splenocytes of mice. These findings demonstrated that hierarchical copper- and zinc- buds dressing γ-AlOOH mesostrands, which are oriented in randomly wrinkled matrice, are suitable platforms as novel adjuvants for cancer immunotherapy.